Lead Isotope Data for Gold-Bearing Veins and Their Host Metasedimentary Rocks of the Goldenville Formation, Eastern Nova Scotia - Farquhar, R.; Haynes, S. (Atlantic Geology, 1986)
Lead isotope analyses have been determined for galenas which occur in small quantities in quartz veins in the Goldenville Formation of the Meguma Terrane, and also for five whole rock samples from this formation- The ten least radiogenic galenas are homogeneous in isotopic composition, and they plot close to the average terrestrial growth curve of Stacey and Kramers and the "orogene" curve of Doe and Zartman. The mean model ages are 550 Ma (Stacey and Kramers) and 600 Ma (Doe and Zartman), which are in approximate agreement with the Cambro-Ordovician age of deposition of the sediments. The close position of the galena compositions to these average growth curves suggests that these compositions were established by mixing processes as envisaged in the Doe and Zartman "plumbotectonics" model. Tne isotopic analyses of the whole rocks indicate that small amounts of radiogenic lead are present in non-mineralized sections of the sedimentary sequence- Three galenas from veins in rocks metamorphosed to biotite and staurolite-andalusite grades, and from late veins (post-dating deformation, metamorphism and plutonism) are significantly more radiogenic than tne majority of the samples. We interpret the isotopic characteristics of these galenas to be the result of extraction of lead from Meguma metasediments or of additions of radiogenic lead to less radiogenic lead during remobllization. Other interpretations consistent with the isotopic data are possible.